THE MULTIPLIER EFFECT OF THE GANDORIAH BEACH MARINE TOURISM TO THE COASTAL COMMUNITY OF KELURAHAN PASIR, CENTRAL PARIAMAN DISTRICT, PARIAMAN CITY WEST SUMATRA PROVINCE - Nurnaini Mazidah; Firman Nugroho; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on March 25, 2016 until 11 April 2016 which is placed in Gandoriah Beach, Kelurahan Pasir, Central Pariaman District, Pariaman City West Sumatra Province. This study aims to identify economic activities and socio-cultural as the impact of the presence of marine tourism and determine the impact of tourism activities on the beach Gandoriah to the economy of coastal communities. The method used in this research is survey method. There are 64 respondents, that consist of 41 visitors, 18 businesses and 5 fisherman.Based on the research results obtained that economic activities undertaken in the Gandoriah Beach marine tourism region are: Restaurants, Cafes, Traders of food and beverages, ship or service provider, Souvenirs, Guard toilet and Parking attendant. Socio-cultural activities that arise due to the presence of the Gandoriah Beach marine tourism are: Beach Party, Weekly Art Display, New Year Night Party and Hoyak Tabuik Party. So that obtained Ratio Income Multiplier value by Type I is 1.37 that means the Gandoriah Beach marine tourism give the more considerable economic impact of the tourism activities.Keywords: Multiplier effects, Gandoriah Beach Marine Tourism, Coastal Communities